2012
DOI: 10.1111/j.1365-2362.2012.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunological response by dendritic cells in male hypogonadism

Abstract: These findings show an enhanced immunological response of circulating (activated) CD16(+) DCs to antigen stimulation, which was inversely related to testosterone and gonadotropin serum levels. Such findings suggest a modulation by the hypothalamic-hypophyseal-gonadal axis of the immune response and may have clinical implications for hypogonadic men, as regards susceptibility to autoimmune diseases and increased responses to antigenic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…Of note, at this time point, the correlation between the gonadotrophin levels and CD107b expression by APC was restricted to the monocytic cell subsets, while absent for the DC subpopulations. These results support and extend our previous observations showing a significant correlation between both testosterone and gonadotrophin serum levels and expression of CD107b on in vitro ‐stimulated PB CD16 + monocytes from untreated hypogonadal men; at the same time, they suggest direct involvement of the FSH receptors recently identified in human monocytic cells . In turn, in vitro studies have shown that exposure to hCG significantly reduces the stimulatory capacity of T‐cells by DC induces a tolerogenic phenotype of DC and contributes to foetal–maternal tolerance during pregnancy, both effects potentially contributing to prevent allogenic T‐cell responses against the embryo.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, at this time point, the correlation between the gonadotrophin levels and CD107b expression by APC was restricted to the monocytic cell subsets, while absent for the DC subpopulations. These results support and extend our previous observations showing a significant correlation between both testosterone and gonadotrophin serum levels and expression of CD107b on in vitro ‐stimulated PB CD16 + monocytes from untreated hypogonadal men; at the same time, they suggest direct involvement of the FSH receptors recently identified in human monocytic cells . In turn, in vitro studies have shown that exposure to hCG significantly reduces the stimulatory capacity of T‐cells by DC induces a tolerogenic phenotype of DC and contributes to foetal–maternal tolerance during pregnancy, both effects potentially contributing to prevent allogenic T‐cell responses against the embryo.…”
Section: Discussionsupporting
confidence: 91%
“…Androgens are generally believed immunosuppressive [23,24], though also have been suggested to have an immuno-modulatory effect, either immuno-enhancing or -suppressive [25]. Assuming immune system-induced increases androgen levels, then such immuno-modulatory effects of androgens may be able to feed back, and self-control androgen production by adrenals and/or ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Following our previous observation about an enhanced immunological response of circulating CD16+ monocytes/ dendritic cells (DCs) to antigen stimulation in male hypogonadism [84], we have recently analysed the effects of testosterone replacement therapy on the immunocellular response of these subjects [85]. Testosterone treatment induced overexpression of LAMP-2 on both classical (CD16-) and nonclassical (CD16+) monocytes/DCs, a very high correlation being observed between LAMP-2 expression on these cells and both the LH and FSH serum levels [85].…”
Section: Enhanced Immunological Response By Dendritic Cells In Male Hmentioning
confidence: 99%